2021
DOI: 10.1111/opn.12416
|View full text |Cite
|
Sign up to set email alerts
|

Assessing acute functional decline in older patients in home nursing care settings using the Modified Early Warning Score: A qualitative study of nurses’ and general practitioners’ experiences

Abstract: Aims and objectives The study describes experiences of registered nurses and general practitioners when using the Modified Early Warning Score (MEWS) to assess acute functional decline in older home nursing care patients. Background Acute functional decline is common among older home nursing care patients; typically characterised by nonspecific symptoms and a mix of manifestations. Early warning score systems for detecting clinical deterioration have been thoroughly evaluated in hospital settings, but few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…This study shows that using SAFE systemizes patient‐centred work and increases nurses' professional self‐confidence. The results are in line with recent studies on assessment tools for physical function which found that the assessment tool MEWS facilitated nurses' clinical reasoning and decision making when acute functional decline was detected in home nursing patients (Jeppestøl et al, 2022 ; Roney et al, 2015 ). The findings of a study by Moi et al ( 2019 ) on the use of ISBAR in clinical practice showed that the participants felt more confident about their ability to quickly obtain an overview of patient situations (Moi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…This study shows that using SAFE systemizes patient‐centred work and increases nurses' professional self‐confidence. The results are in line with recent studies on assessment tools for physical function which found that the assessment tool MEWS facilitated nurses' clinical reasoning and decision making when acute functional decline was detected in home nursing patients (Jeppestøl et al, 2022 ; Roney et al, 2015 ). The findings of a study by Moi et al ( 2019 ) on the use of ISBAR in clinical practice showed that the participants felt more confident about their ability to quickly obtain an overview of patient situations (Moi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Heart rate was the second most frequent deviating vital sign in the habitual state (19.6%), a result supported by research showing that an increased resting heart rate is common in the habitual state of older persons (Coupé et al, 2009 ). However, studies have also shown that slightly increased respiratory rate and/or heart rate are associated with possibly higher levels of clinical responses and death (Bunkenborg et al, 2019 ; Jeppestøl et al, 2021b ). This study contributes important knowledge that elevated respiratory‐ and/or heart rate may represent a combination of physiological normal aging processes and chronic diseases, as well as acute disease for older multimorbid home nursing care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has investigated staff experiences using the EWS in prehospital, primary care and community settings (Brangan et al, 2018) and among older patients in cases of acute functional decline in home nursing care (Jeppestøl et al, 2022b).…”
Section: Ews With Clinical Deteriorationmentioning
confidence: 99%
See 2 more Smart Citations